Extraction of carotenoid pigments as shariah compliant food colorants through cell culture of freshwater green microalgae (Chlorophyta) and Cyanobacteria - Nur Hidayah binti Noh (International Institute for Halal Research and Training (INHART), International Islamic University Malaysia, 2017)
Nowadays, halal products are gaining wider recognition as a new benchmark for safety and quality assurance. As a consequence the commercial development of microalgae are established due to their high value chemicals, for examples, β-carotene, astaxanthin, phycobilin pigments and algal extracts for cosmaceuticals products. Therefore, many researchers have gained interest to study the potential of microalgae as new valuable chemicals and other products sources. The aim of the research is to explore new sources of pigments to be used as halal food colorants. This quest is not only directed in finding natural alternatives for synthetic dyes, but also to discover new taxons for the carotenoid production. Thus, there is a solid need to investigate the potential of natural pigments particularly carotenoids in microalgae to be fully utilised and commersialised especially in halal market, health advantages, food products and dye technology. A total of 10 species were evaluated for quantitative and qualitative carotenoid composition namely Chlorella fusca, Chlorella vulgaris, Selenastrum capricornutum, Pandorina morum, Butyriciococcus sudeticus ,Chlorococcum, Pseudanabaena, Scenedesmus, Ankistrodesmus, and Butyrocicoccus Brauni.Chlorella fusca (chlorophyta) and Pseudanabaena(cyanobacteria) and found three types of carotenoid out of them which are β-carotene, β-carotene and lutein. Species that was having all three types of carotenoid was Pandorina morum (Figure 4.8) with lutein (54.64±3.11 mg/g DW) , Beta cryptoxanthin (2.38±0.56 mg/g DW) and Beta carotene (1.39±0.38 mg/g DW) Manipulation of nutrient and nitrate concentration, manipulation of carbon sources. Two types of microalgae were choosen represent their division which are Chlorella fusca (Chlorophyta) and Pseudanabena (Cyanobacteria) were subjected to nutrient and manipulation stress studies. There were cultured using Bold's Basal Medium (BBM), Bristol medium and Bold's Basal Medium (BBM) modified with vitamin B with different nutrient and carbon sources. There were three types of carotenoid had produced which are zeaxanthin (21248.7 ± 240.61mg/g DW), violaxanthin (16299±423.09mg/g DW) and lutein (2335.53±69.82mg/g DW) with their highest number respectively. Nitrate concentration also been manipulated in all types of medium that been used and it had produced lutein. The highest lutein number was produced in cultivation of Pseudanabaena in Bristol medium with 0.5 fold nitrate concentration (1317.91±40.13mg/g DW). Chlorella fusca and Pseudanabena also been cultured in BBM with the addition of different elicitors which are salicylic acid (SA), polyethylene glycol (PEG) and sodium chloride (NaCl). All of these elicitors had initiate production of lutein. Among of those three elicitors, this studies had found that the implication of 25mg/L of SA had yield highest lutein concentration (666.45±24.66mg/g DW).Cell concentration of microalgae also been recorded for all studies except for profiling. Cell count were done using haemocytometer under microscope and growth pattern of microalgae been plotted to monitor microalgae cell density